2012
DOI: 10.2174/1874192401206010050
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 in Early Flow-Related Remodeling of Mesenteric Arteries from Young Normotensive and Spontaneously Hypertensive Rats

Abstract: We tested the hypotheses that TSP-1 participates in the initiation of remodeling of small muscular arteries in response to altered blood flow and that the N-terminal domain of TSP-1 (hepI) can reverse the pathological inward remodeling of resistance arteries from SHR.We measured (1) changes in gene/protein expression in MA of 6 week old WKY and SHR exposed to either increased (+ 100 %) or reduced blood flow (- 90 %) for 24-40 hours and (2) structural changes in MA of 12 week old SHR exposed for 3 days to hepI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…6,16,18 Increased TSP-1 levels have also been noted in patients 16 and rats with hypertension. 24 Studies have also reported that TSP-1 may represent a link between vascular risk factors and vascular atherosclerotic lesion development . 17,25 Hypertension is a major driving force and a modifiable risk factor for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…6,16,18 Increased TSP-1 levels have also been noted in patients 16 and rats with hypertension. 24 Studies have also reported that TSP-1 may represent a link between vascular risk factors and vascular atherosclerotic lesion development . 17,25 Hypertension is a major driving force and a modifiable risk factor for atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the balloon catheter injury rat model, TSP was markedly increased in the thickening arterial wall, and the TSP antigen in thickening arterial wall is primary secreted by VSMcs (118). In rat resistance arteries, TSP-1 was able to reverse the pathological inward remodeling caused by spontaneous hypertension, indicating that TSP-1 may act as an inhibitor of arterial restenosis (119). A previous study identified that the interaction of TSP-1 and β1 integrin is associated with platelet-stimulated SMc proliferation (120).…”
Section: Arterial Restenosismentioning
confidence: 95%
“…Thrombospondin-1 (TSP-1) is involved in structural remodeling in large and small arteries [ 129 , 130 ]. Physiological levels of TSP-1 increased Superoxide production and decreased NO-dependent vasodilation more in coronary arterioles from old female rats than in young females [ 131 ].…”
Section: Potential Molecular Mechanisms In Age-dependent Structural R...mentioning
confidence: 99%